دور المعاملات الإلكترونية في ترقية جودة الخدمات في ظل الازمة الصحية جائحة كورونا دراسة ميدانية في البنك الخارجي الجزائري/-والبنك الجزائري/بنك الفلاحة والتنمية الريفية - رجاء بصيود; شمس الضحى احمد جبالي (My University, 2021)
This study exposes the concept of electronic transactions, and clarifies the importance of its use at the level of banks and financial institutions, so that it shows us the great importance that banking systems enjoy with regard to financial transactions, and it also tries to address its most important aspects in the field of banking services, in addition to defining its reality and requirements for its use. On the part of Algerian banks, and their effectiveness in keeping pace with the progress of development and knowing the great impact that electronic transactions play in banks by improving the quality of their services, which enhances the relationship between the bank and the customer, and stands on the most important challenges facing benefiting from them in meeting the needs of customers ........................................................... تتعرض ىذه الدراسة إلى مفهوم المعاملات الإلكترونية ، وتوضح أهمية استخدامها على مستوى البنوك و المؤسسات المالية ، بحيث تبين لنا الأهمية الكبيرة التي تتمتع بها الأنظمة البنكية فيما يخص المعاملات المالية ، وتحاول أيضا التطرق إلى أىم مظاىرىا في مجال الخدمات المصرفية، بالإضافة إلى تحديد واقعها ومتطلبات استخدامها من طرف البنوك الجزائرية، ومدى فعاليتها في مواكبة سير التطور ومعرفة الأثر الكبير الذي تلعبو المعاملات الإلكترونية في البنوك من خلال تحسين جودة خدماتها ما يعزز العلاقة بين البنك والعميل ، و الوقوف على أىم التحديات التي تواجو الاستفادة منها في مجال تلبية احتياجات العملاء